2015
DOI: 10.1155/2015/849308
|View full text |Cite
|
Sign up to set email alerts
|

ICT Learning by Older Adults and Their Attitudes toward Computer Use

Abstract: Information and communication technologies have proven to be an effective way of helping older adults improve independence outcomes, but such technologies are yet not widely used by this segment of the population. This paper aims to study computer use and senior citizens' attitudes toward computer technology in the context of a 20-hour course in basic skills. A questionnaire was used to conduct pre- and postcourse analyses with a sample of 191 adults over the age of 60. The findings show that direct contact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 33 publications
(32 reference statements)
1
42
0
3
Order By: Relevance
“…Methods: Survey in Lower Saxony -Contemporaneous digital technologies get older too, the today one which usage is learned in schools will be different when learners will reach their 80s. (González, Ramírez, & Viadel, 2015) Aim: Senior' attitudes toward computer technology in the context of a 20-hour course in basic skills. Methods: A questionnaire applied pre-and post-course -sample of 191 adults over the age of 60.…”
Section: Research Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods: Survey in Lower Saxony -Contemporaneous digital technologies get older too, the today one which usage is learned in schools will be different when learners will reach their 80s. (González, Ramírez, & Viadel, 2015) Aim: Senior' attitudes toward computer technology in the context of a 20-hour course in basic skills. Methods: A questionnaire applied pre-and post-course -sample of 191 adults over the age of 60.…”
Section: Research Methodology and Resultsmentioning
confidence: 99%
“…(Berry, 2011) even declares that the education level should be incorporated as a map of reasons for digital exclusion. Papers were also identified (González, Ramírez, & Viadel, 2015), (Cimperman & et al, 2016) that concluded a insignificant or neutral influence of education level upon the elders' acceptance for digital technologies, declaring that even older people with a low level of education modify their attitudes positively toward new technologies when they are motivated by application (learning, connecting to others, entertainment). The reason for this influence would lie not in the specific skills of using the technology (that were not delivered in school long before) but in the development of so called "crystallized intelligence" (Czaja & et al, 2006), wich level is determined by the initial education level and has the ability to strongly diminish the negative atitude towards technology (computer anxiety).…”
Section: Influence Of Education Level On Elderly Acceptance Of Digitamentioning
confidence: 99%
“…Although many CALD patients are non-computer users, possibly because they had few opportunities to acquire computer skills during their education and work [46,47], they are not completely disadvantaged in mobile technology use, particularly not in smart phone use. Consistently, smart phone ownership has been found to be the highest among CALD groups [48], which offers great promise for implementing smart phone based interventions in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mandarin speaking patients are less likely to use emails compared to English speaking patients. Therefore, email based communication in CVD secondary prevention might not be feasible among certain CALD groups [46]. Selecting an appropriate delivery method for CR interventions is the key to improving participation amongst CALD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In both scenarios, the existence of this gap correlates with the users' age and could mean disadvantages and exclusion for the elderly. Moreover, Prensky's view has been challenged by different studies because of its simplification of the relation between age and ICT appropriation (Helsper and Eynon (), R. González, Ramírez, and Viadel (), Jones, Shao, and Keynes ().…”
Section: Understanding Generational Differences In Internet Appropriamentioning
confidence: 99%